Acesso à justiça do trabalho: Antes e depois da reforma trabalhista - Alexandre dos Santos Cunha; Paulo Eduardo Alves Da Silva; Adriana Avelar Alves; Carla Rodrigues Costa De Araújo; Danielle Zoega Rosim; Ana Flavia Lopes de Moraes Toller; Gustavo Lima De Paula; Victor Dantas de Maio Martinez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Federal Statute no 13.147, enacted by National Congress in July 13th, 2017, altered extensively the Brazilian Labour Code. Several of the alterations were justified under the need to solve legal certainty issues, that allegedly caused excessive labour litigation. In the same direction, changes were also made in labour dispute resolution procedures, in order to undermine a worker plaintiffs alleged opportunistic behavior in courts. Immediately after the Reform, there was a significant reduction in the number of new cases presented to labour courts. Comparing the characteristic of the cases presented before the Reform, registered at the National Database of Settled Labour Disputes, which represents the labour lawsuits settled in 2012, this paper proposes itself to understanding the differences between the cases presented before and after the Reform, investigating if these differences may be explained by the advent of the Reform, or not.
Keywords: J52; K31; K41; 330; labour dispute resolution; labour reform; access to justice